COMPARISON OF ONLINE VS CLASSROOM DELIVERY OF UNDERGRADUATE BASIC MEDICAL SCIENCES MODULE - Fouzia Hanif; Fatima Ehsan; Nasim Ilyas; S.Khan, Safia (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: Corona virus disease (Covid-19) pandemic has impacted lives and institutes globally with serious consequences. No doubt universities are facing immense challenges in this transition to online education. To evaluate the effectiveness of online system of teaching in Covid 19 pandemic as compared to classroom teaching in a basic medical sciences module. METHODOLOGY: This cross-sectional study was conducted at Islamic International Dental College, from 15th February to 15th May 2020 on 1ST year BDS students. At the end of their online module, an online feedback questionnaire was given to students. Assessment of the online module was compared with the previous class module assessment to get an insight of their performance. SPSS version 25 was used. Student’s t test was used. RESULTS: A highly significant p value was found in both Physiology and Biochemistry online tests as compared to class tests. Regarding feedback, 63(91.3%) students preferred classroom teaching as it enhanced active participation 59 (85.5%) and student teacher engagement 62 (89.9%). Students agreed that queries were addressed during online sessions 57 (70.9%) but they seemed less motivated 21(30.4%) and grasping of difficult concepts was tough 48 (69.5%). Teachers seemed more enthusiastic in online teaching 52 (75.4%), but there was variety of teaching tools used in classroom sessions 65 (94.2%). CONCLUSION: Gradually medical universities, faculty and students will adapt with the e-learning but we need to implement innovative and proactive measures for students and faculty to enhance students learning.